We have the equation ax^2 + 8x + 12 = 0.

The roots of a quadratic equation ax^2 + bx + c = 0 are x1 = [-b + sqrt (b^2 – 4ac)]/2a and x2 = [-b - sqrt (b^2 – 4ac)]/2a.

Here one of the roots is twice the other

=> [-b + sqrt (b^2 – 4ac)]/2a = 2*[-b - sqrt (b^2 – 4ac)]/2a

=> [-8 + sqrt (8^2 – 4*12*a)]/2a = 2*[-8 - sqrt (8^2 – 4*12*a)]/2a

=> [-8 + sqrt (8^2 – 4*12*a)] = [-16 – 2*sqrt (8^2 – 4*12*a)]

=> -8 + 16 + 3* sqrt (8^2 – 4*12*a) = 0

=> 8 + 3* sqrt (8^2 – 4*12*a) = 0

=> 3* sqrt (8^2 – 4*12*a) = -8

square both the sides

=> 9*(8^2 – 4*12*a) = 64

=> 9*64 – 9*48*a = 64

=> 9* 48* a = 64*8

=> a = 32/27

**Therefore if a is 32/27 in the quadratic equation ax^2 + 8x + 12 = 0, one root is twice the other.**

## We’ll help your grades soar

Start your 48-hour free trial and unlock all the summaries, Q&A, and analyses you need to get better grades now.

- 30,000+ book summaries
- 20% study tools discount
- Ad-free content
- PDF downloads
- 300,000+ answers
- 5-star customer support

Already a member? Log in here.

Are you a teacher? Sign up now